European bees of the genera Epeolus Latreille, 1802 and Triepeolus Robertson, 1901 (Hymenoptera: Apidae: Nomadinae: Epeolini): taxonomy, identification key, distribution, and ecology - Bogusch, Petr; Hadrava, Jiří (Zootaxa, 2018)
Seventeen species of Epeolus Latreille, 1802 and one species of Triepeolus Robertson, 1901 have been recorded from Europe. Members of these genera are cuckoo bees, cleptoparasites that appropriate provisions of other bee genera (Colletes Latreille [hosts of Epeolus] and Tetraloniella Ashmead [hosts of Palaearctic Triepeolus]) for their own offspring. We present an identification key to all European species plus four species known from neighbouring regions (the Middle East and North Africa) that might also occur in Europe. The taxonomy of all species is reviewed, with new synonymies proposed, one subspecies elevated to a species (Epeolus eriwanensis Bischoff, 1930, stat. nov.), and a new species (Epeolus ibericus Bogusch, sp. nov.) described. Five new synonymies are proposed: E. giannelli Gribodo, 1894 syn. nov. and Epeolus speculifer Pérez, 1895 syn. nov. under E. fallax Morawitz, 1872, E. berlandi Benoist, 1943 syn. nov. and E. laevigatus Bischoff, 1930 syn. nov. under E. flavociliatus Friese, 1899, and E. julliani Pérez, 1884 syn. nov. under E. transitorius Eversmann, 1852. The following species are redescribed because their identity is less clear due to type specimens and/or vague original descriptions: Epeolus aureovestitus Dours, 1873, Epeolus cruciger (Panzer, 1799), Epeolus fallax Morawitz, 1872, Epeolus schummeli Schilling, 1849, Epeolus siculus Giordani Soika, 1944, and Epeolus variegatus (Linnaeus, 1758). Males are described for the first time for the following species: Epeolus compar Alfken, 1938, Epeolus eriwanensis Bischoff, 1930, Epeolus intermedius Pérez, 1884, Epeolus laevifrons Bischoff, 1930, and Epeolus subrufescens Saunders, 1908. Distribution maps created using records from the literature and data from private and museum collections are also provided, which show changes in the distributions of epeoline bees before and after 1990. Several species are considered endangered, especially Epeolus fasciatus Friese, 1895, which is nearly extinct, and Epeolus tarsalis Morawitz, 1874, which was recently reported only from the coastal parts of the Netherlands and Belgium. Epeolus variegatus is the only common and widespread species still encountered in most of Europe. Comprehensive information on the ecology of these cuckoo bees is also included.